How to prove the following trigonometric identities ?

1) If $\displaystyle \tan (\alpha) \cdot \tan(\beta) = 1 \text{ then } \alpha + \beta = \frac{\pi}{2}$

I tried to prove it by using the the formula for $\tan(\alpha + \beta)$ but ain't it valid only when $\alpha + \beta \neq \frac{\pi}{2}$ ?

2) $\displaystyle\sec\theta + \tan \theta = \frac{1}{ \sec\theta - \tan \theta}, \theta \neq (2n+1)\frac{\pi}{2}, n \in \mathbb{Z} $

For this one I tried substituting them with the sides of the triangle, but not successful to the final result.

These are not my homework, I am trying to learn maths almost on my own, so ...

  • $\begingroup$ @Tretwick Marian: The fist one should be $\tan(\alpha) \tan(\beta) = 1$, then $\alpha + \beta = \frac{\pi}{2}$. The second one should be $\displaystyle\sec\theta + \tan \theta = \frac{1}{ \sec\theta - \tan \theta}, \theta \neq (2n+1)\frac{\pi}{2}, n \in \mathbb{Z} $. $\endgroup$ – user17762 Nov 27 '10 at 8:08
  • 1
    $\begingroup$ Unless there are restrictions on $\alpha$ and $\beta$, the first conclusion is not correct; it should be $\alpha+\beta=\pi/2+n\pi$ for some integer $n$. $\endgroup$ – Hans Lundmark Nov 27 '10 at 14:09
  • $\begingroup$ The first equality is not an identity. Perhaps the title should be changed. $\endgroup$ – Américo Tavares Nov 27 '10 at 16:00

Added (and corrected twice):

$$\tan \alpha \tan \beta =1\Leftrightarrow \dfrac{\sin \alpha }{\cos \alpha }% \dfrac{\sin \beta }{\cos \beta }=1$$

Multiplying by $\cos\alpha\cos\beta\ne 0$, gives

$$\sin \alpha \sin \beta -\cos \alpha\cos \beta =0 \Leftrightarrow \cos (\alpha +\beta )=0$$

This is equivalent to

$$\alpha +\beta =\dfrac{\pi }{2}+n\pi,\qquad (\ast)$$

to which we still have to add the condition written above ($\cos\alpha\cos\beta\ne 0$), which means the constraint

$$\alpha,\beta\ne\dfrac{\pi}{2}+n\pi,\qquad (\ast\ast)$$

where $n$ is an integer.

Note: In the original equation $\tan \alpha \tan \beta =1$, neither $\alpha$ nor $\beta$ can be zero. The combined conditions $(\ast)$ and $(\ast\ast)$ assures that.

The identity $$\sec \theta +\tan \theta =\dfrac{1}{\sec \theta -\tan \theta }\qquad \theta \neq (2n+1)\dfrac{\pi}{2}$$

is equivalent to $$\sin ^{2}\theta +\cos ^{2}\theta =1.$$

Indeed, if

$$\theta \neq (2n+1)\dfrac{\pi }{2}\Leftrightarrow \sin \theta \neq \pm 1 \Leftrightarrow \dfrac{\pm1}{\cos \theta }-\dfrac{\sin \theta }{\cos \theta }\neq 0\Leftrightarrow \pm\sec \theta -\tan \theta \neq 0,$$


$$\sec \theta +\tan \theta =\dfrac{1}{\sec \theta -\tan \theta }\Leftrightarrow \left( \sec \theta +\tan \theta \right) \left( \sec \theta -\tan \theta \right) =1$$

$$\Leftrightarrow \sec ^{2}\theta -\tan ^{2}\theta =1\Leftrightarrow \dfrac{1}{\cos ^{2}\theta }-\dfrac{\sin ^{2}\theta }{\cos^{2}\theta }=1\Leftrightarrow 1-\sin ^{2}\theta=\cos ^{2}\theta$$ $$\Leftrightarrow \sin ^{2}\theta +\cos ^{2}\theta =1.$$

  • 1
    $\begingroup$ There are several errors in the first computation; for example, in the second step you have three $\alpha$'s and one $\beta$. $\endgroup$ – Hans Lundmark Nov 27 '10 at 14:05
  • $\begingroup$ @Hans Lundmark, Many thanks! I have corrected them. $\endgroup$ – Américo Tavares Nov 27 '10 at 14:47
  • $\begingroup$ Fine, except that there is one step where equivalence doesn't hold (see the comments to user3971's answer), and you've forgotten to add $n\pi$ at the end. $\endgroup$ – Hans Lundmark Nov 27 '10 at 15:01
  • $\begingroup$ @Hans Lundmark, I corrected once more the first computation. $\endgroup$ – Américo Tavares Nov 27 '10 at 15:35
  • $\begingroup$ @Tretwick Marian, concerning the first equation, please look at the new solution I wrote after you has accepted my answer. $\endgroup$ – Américo Tavares Nov 27 '10 at 16:39

When I need to prove trigonometric identities, I tend to use complex exponentials. For instance, to prove your first identity observe that \begin{align} \sin \theta = \frac{e^{i \theta} - e^{-i \theta}}{2i} \quad \text{and} \quad \cos \theta = \frac{e^{i \theta} + e^{-i \theta}}{2}, \end{align} so \begin{align} \tan \theta = \frac{1}{i} \frac{e^{i\theta} - e^{-i\theta} }{e^{i \theta} + e^{-i \theta}}. \end{align} We calculate \begin{align} 1 = \left( \frac{1}{i} \frac{e^{i\alpha} - e^{-i\alpha} }{e^{i \alpha} + e^{-i \alpha}} \right) \left(\frac{1}{i} \frac{e^{i\beta} - e^{-i\beta} }{e^{i \beta} + e^{-i \beta}} \right) = - \frac{(e^{2 i \alpha} - 1)(e^{2 i \beta} - 1)}{(e^{2 i \alpha} + 1)(e^{2 i \beta} + 1)} \end{align} Hence, \begin{align} (e^{2 i \alpha} + 1)(e^{2 i \beta} + 1) = - (e^{2 i \alpha} - 1)(e^{2 i \beta} - 1). \end{align} or $e^{2 i (\alpha + \beta)} + 1 = 0$, which implies that $\alpha + \beta = \frac{\pi}{2}$ by Euler's equation $e^{\pi i} + 1 = 0$, provided that we consider only angles in the fundamental region $[-\frac{\pi}{2}, \frac{\pi}{2}]$. A similar calculation works for your second identity.


1) tan(a)tan(b) = 1 is equivilant to sin(a)sin(b) = Cos(a)cos(b) **using the fact that tan is sine divided by cosine. Next use cos(a+b) = cos(a)cos(b) -sin(a)sin(b)

which implies sin(a)sin(b) = cos(a)cos(b) -cos(a+b)

Use this on the left hand side of ** to get

                              cos(a+b) = 0

which implies a+b = Pi/2 or -Pi/2

  • 5
    $\begingroup$ -1: First, tan(a)tan(b) = 1 and sin(a)sin(b) = cos(a)cos(b) are not equivalent. Second cos(a+b)= 0 does not imply a+b = pi/2 or -pi/2. $\endgroup$ – Aryabhata Nov 27 '10 at 8:33
  • 1
    $\begingroup$ btw, you have the right idea :-). So please edit the answer to correct the mistakes so that I can upvote. $\endgroup$ – Aryabhata Nov 27 '10 at 8:41
  • $\begingroup$ @Moron: I am not getting your first comment.Please explain :) $\endgroup$ – Quixotic Nov 27 '10 at 10:32
  • 2
    $\begingroup$ @Debanjan: The implication only goes one way; for example, if $a=0$ and $b=\pi/2$ the equation with sin & cos is satisfied, but not the one with tan. And $\cos x=0$ iff $x=\pi/2+n\pi$ where $n$ is an arbitrary integer (not just $n=0$ or $n=-1$). $\endgroup$ – Hans Lundmark Nov 27 '10 at 14:58
  • $\begingroup$ Hmm,...,got it. $\endgroup$ – Quixotic Nov 27 '10 at 18:57

For (2)

$$\sec \theta + \tan \theta = \frac{1}{\cos \theta} + \frac{\sin \theta}{\cos \theta}= \frac{1 + \sin \theta}{\cos \theta}$$ $$ = \frac{(1 + \sin \theta)\cdot (1 - \sin \theta)}{\cos \theta \cdot(1 - \sin \theta)}\text{ [Multiplying both sides by } (1 - \sin \theta)\text{]} $$ $$ = \frac{\cos^2 \theta}{ \cos \theta - \sin \theta \cdot \cos \theta} = \frac{1}{\sec \theta - \tan \theta} \text{ (Q.E.D) }$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.